Perception and Motivation of Students Towards the Implementation of Indonesian Great Children's Gymnastics in Elementary Schools - Winda Sri Wahyuliana; Recky Ahmad Haffyandi; M. Mulhim (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to examine students’ perceptions and motivations towards the implementation of theGreat Indonesian Children’s Gymnastics program in elementary schools. The method used is a survey with a descriptive quantitative approach. The research population is all students of State Elementary School  Jawa 5 Martapura, with a purposive sample of 70 students from grades 5 and 6. The instrument used is a Likert scale-based questionnaire to measure students’ perceptions and motivationData analysis was conducted using descriptive statistics in the form of percentages and categorization based on the mean and standard deviation. The research results show that the majority of students have perceptions and motivations in the moderate to high category regarding the implementation of Great Indonesian Children’s Gymnastics. However, there are still students with low perceptions and motivation, indicating challenges in the implementation of this program. The differences in levels of perception and motivation are influenced by the understanding of the benefits of exercising, implementation methods, and individual interests. In conclusion, Great Indonesian Children’s Gymnastics has the potential to become part of a healthy lifestyle culture for students if implemented with a more engaging, educational approach that suits the characteristics of elementary school-aged children.